Study of analgesia using bupivacaine as local infiltration in cholecystectomy - Kuradagi, Shridhar; Navalli, Krishnareddy (International Surgery Journal, 2016)
Background: Minimally invasive procedures hold an important position in nowadays’ surgical practice. Laparoscopic cholecystectomy has become the main treatment of symptomatic cholelithiasis. Post-operative pain management has been a constant challenge to many of the surgeons. Effective relief of pain has got physiological and psychological benefits. Because of their side effects most of the analgesic dosage is inadequate. There is need for developing newer modalities which can provide good analgesia with fewer side effects. The objective of the study was to compare preemptive and preclosure infiltration of bupivacaine in reducing post operative pain and analgesic requirement. Methods: Double blind randomized clinical trial was done in GIMS Hospital Gadag. Total of 40 patients, 20 undergoing open Cholecystectomy, 20 undergoing laparoscopic Cholecystectomy were included in study. Post-operative pain measured using numerical VAS and amount of analgesic use. Results: In open Cholecystectomy there was significant difference in pain score at 3rd hr and 6th hr. Requirement of rescue analgesia occurred early in preclosure group and also the numbers of doses required were more when compared to preemptive grou. Requirement of rescue analgesia occurred early in preclosure group and also there was significant difference in analgesic requirement at 6th hr and at 10th hr. Conclusions: Preemptive infiltration is helpful in delaying first dose of analgesic and decreasing the number of analgesic doses in first 48 hrs postoperatively in open cholecystectomy. Preemptive infiltration of bupivacaine delays the time duration for the requirement of first analgesic dose and may also be helpful in reducing the number of analgesic doses in postoperative period when compared to preclosure infiltration in common abdominal surgeries.